Hubungan Faktor Risiko Depresi dengan Tingkat Depresi pada Gay, Transgender, dan LSL - Resati Nando Panonsih; Ika Artini; Arif Effendi; Aradhea Kumala Azizah (ARTERI : Jurnal Ilmu Kesehatan, 2020)
Health problems experienced by gay, transgender, and MSM (Men who have Sex with Men) one of the psychological problems such as depression. The social problems that they often experience are stigma and discrimination, including access to health services. The risk factors of depression are genetic, age, and psychosocial factors. This study conducted to determine the relationship between risk factors of depression with levels of depression to the gay, transgender, and MSM in Bandar Lampung 2019. Methods: The type of research is an analytic survey with a cross-sectional. The samples were taken using total sampling. The subjects in this research are all 35 members of the Gaya Lentera Muda Organization. The type of data obtained is primary data. The results of this research that from 35 subjects is obtained the subjects with middle education mostly have mild depression of 7 subjects (36,8%). The subjects who have an occupation mostly have mild depression of 6 subjects (33,3%). The subjects who have genetic factors mostly have severe depression of 13 subjects (72,2%). There is a meaningful relationship between genetic factor (p value= 0,000) and psychosocial factor (education level p value= 0,040 and employment status p value= 0,050) with levels of depression to the gay, transgender, and MSM (Men who have Sex with Men). There is no relationship between age factor (p value= 0,856) with levels of depression to the gay, transgender, and MSM (Men who have Sex with Men).